Participação social na elaboração de estratégias para reduzir o consumo e gastos da administração pública com energia elétrica - Souza, Wagner Vilas Boas de (2015)
This work considers the increasing demand in Brazil for electric energy, as well as the unsustainable circumstances of worldwide energy matrix and representation of expenses with electric energy intake in the Other Costs and Capital Budget Matrix (OCC Matrix) of Federal Education Institutions (FEIs) in Brazil. We aimed at evaluating innovative ideas that allow the FEIs to reduce expenses with energy intake by means of social participation. Thus, the main issue of this research was: how to reduce expenses with energy intake in the Federal Education Institutions using social participation? To do this, the Ministry of Education (MEC) created the Sustainability Challenge Project, which constitutes of a public consultation based on the concepts of social participation and crowdstorm aimed at the communities that relate to the 104 Brazilian FEIs. Over 91 days of consultation, with the engagement of all FEIs, MEC identified 9.6 thousand ideas that, together, received 1.1 million evaluations (likes) and 860 thousand comments. An technical interdisciplinary committee evaluated, selected and prioritized this content, allowing editing by the MEC of a collection of solutions, instituted by the Decree MEC no 370, of April 16th of 2015, and launched in the International Congress of Education Innovation Management of the Public Sector (CIGISP), in Brasília. The results of this project showed that social participation contributes in not only identifying and prospecting solutions, but also to mobilize and raise awareness the communities, academics or otherwise, regarding the theme. Despite this work not contemplating the implementation of the solutions, we verified that the reduction in the expenses from the FEIs depends on actions involving other actors in addition to the institution. In this sense, social participation can directly contribute in involving and engaging these actors.